Pemaknaan cerita rakyat Brayut: Dari ideologi agraris hingga kapitalis - I Wayan Budi Utama (Pusat Kajian Bali Universitas Udayana, 2017)
Brayut is one of Balinese folktale that tells about a farmer’s family life with many children. The setting relates to the celebration of Galungan day. By the time being, this story always exists and develops until today. This folktale has been undergoing certain process of construction, deconstruction, and reconstruction of ideology. This paper concerns the ideology implied by the character of Brayut since the traditional until this postmodern era. The research data was collected through the observation, interview, and document study techniques. The analysis was based on the theory of ideology by Thomson supported by the theories of religion. The descriptive-interpretative method was applied to analyze the data. Based on the analysis the results show that this folklore of Brayut has been always reinterpreted since the traditional/agriculture era until this postmodern era. Therefore, the existence of this story may be everlasting until today.